Apixaban vs Warfarin: Safety In Patients with Advanced Kidney Disease - Tanveer, Ahsan; Mehmood, Khalid; Hussain, Mehmood; Zaid, Farhan; Tariq, Soban Ahmed; Aslam, Aakash (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the safety of Apixaban and Warfarin in patients suffering from advanced chronic kidney diseaseStudy Design: Comparative Cross-sectional studyPlace and Duration of Study: Department of Medicine and Nephrology Pak Emirates Military Hospital Rawalpindi, Pakistan from Aug 2021 to Jul 2022.Methodology: A total of 135 cases of advanced chronic kidney disease (stage IV and V) requiring anticoagulation for deep venous thrombosis or atrial fibrillation were recruited in the study. They were randomly divided into two groups. Patients in group I received Apixaban while patients in group II received Warfarin for anticoagulation. They were followed up for three months to look for safety. Major bleeding, Fatal bleeding, non-fatal major bleeding at a critical site and other non-fatal bleedings were compared in both the groups for three months of treatment with the assigned medication.Results: Out of 135 patients of advanced chronic kidney disease managed for atrial fibrillation or deep venous thrombosis, 70(55.6%) patients were males and 55(44.4%) were females. 66(48.9%) took Apixaban while 69(51.1%) took Warfarin for anticoagulation. Bleeding related adverse effects like major bleeding, fatal bleeding, non-fatal major bleeding at a critical site and other non-fatal bleedings were not statistically significant in both the groups (p-value>0.05). Conclusion: Both medications were relatively safe and rate of different types of bleeding was quite low in both the groups. Both medications turned out to be not very different in terms of safety profile in patients suffering from advanced chronic kidney disease.